The responsibility and independence of shari'ah advisors and the shari'ah review process in the Indonesian Islamic banks - Syafei, Ade Wirman (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2005)
The Islamic bank (lB) requires an independent and credible body which ensures that a1l of the IB's activities and transactions are in accordance with Shari'ah principles. Despite the present rules and guidelines developed by National Shari'ah Council - Indonesian 'Ulama Council (NSC-lUC) and Bank Indonesia, there is a lack of sufficient guidelines related to the existence of Shari'ah Advisors (SAs) in Islamic banks (IBs) in Indonesia. Therefore, this study is designed to examine the perceptions of IBs managers and SAs of IBs in Indonesia on the responsibility and independence of SAs, and the Sharf'ah review process. The study utilizes questionnaires to obtain the perceptions of IB managers while it uses interview to obtain the perceptions of SAs of lBs in Indonesia. There are 67 IB managers and 5 SAs of IBs in Indonesia who are actively involved as the respondents of the study. The study shows that the respondents perceived that the SAs are responsible for ensuring that the products, contracts and transactions of IBs are in compliance with Shartah prindples. In order· to improve the independence of SAs, the respondents viewed that the SAs should be proh1bited from becoming consultants and majority shareholders of the IBs for the same IBs in which they act as SAs. The respondents also perceived that the SAs should conduct a Shari'ah review based on a sampling method. After conducting a Shari'ah review, the respondents were of the opinion that SAs should prepare a Sharf'ah review report published in the annual report for the shareholders. In addition the respondents also viewed that SAs should prepare a special Shari'ah review report for the directors, regulators (e.g. Bank Indonesia) and the NSC-IUC. Furthermore, the study indicates that there are some significant differences between the perceptions of Islamic Commercial Bank (ICB) and Conventional Bank that offers an Islamic banking scheme (CBI) on certain aspects related to the responsibility and independence of SAs and the Shari' ah review process in the IBs in Indonesia.